PERLINDUNGAN HAK PEKERJA MIGRAN SEKTOR KONSTRUKSI DI SINGAPURA SELAMA MASA PANDEMI COVID-19 TAHUN 2020 - Ariela Naomi Syifa (2021)
The presence of COVID-19 is a tangible form of the occurrence of a world health crisis in the 21st century era. This virus also has a significant impact on all aspects of the world's people's lives, including migrant workers. The problem of unequal health services for migrant workers is a crucial problem where this is certainly related to the rights they should receive as human beings. Singapore is one country that has experienced this. This study focuses on the conditions experienced by Singaporean construction sector migrant workers who live in dormitories with health and accommodation facilities that have not been able to protect them from the health crisis that hit with a periodization from early 2020 to the making of policy recommendations on the 13th AFML in November 2020. This different treatment of course occurs due to several factors, one of which is the perspective in viewing migrant workers who are only limited to economic entities without taking into account that there are still human rights that need to be equally protected. This is reflected in the not many agreements on the protection of migrant workers that Singapore has ratified, and the migration system from Singapore which has not focused much on protecting the rights of migrant workers. This problem presents various international relations actors such as NGOs to ASEAN regional institutions to jointly help solve problems by submitting various policy recommendations so that with these arguments it can be seen from the presence of joint-discussions between non-state actors and the 13th AFML organized by ASEAN. The author then uses the concepts of Human Rights, Labor Migration, and Transnational Society in explaining this case stud